Study Optoelectronic Properties of Ag2O Heterojunction Prepered by Thermal Oxidation Technique - Khalid Z. Yahia (Engineering and Technology Journal, 2008)
Highly (101)-oriented p-Ag2O thin film with high electrical resistivily was grown bythermal oxidation (TO) on clean monocrystalline p-type Si without any post- depositionannealing. From optical transmittance and absorptance data, the direct optical band gapwas found to be 1.4eV. The electrical and photovoltaic properties of Ag2O/Si isotopeheterojunction were examined in the absence of any buffer layer. Ideality factor ofheterojunction was found to be 3.9. Photoresponse result revealed that there are two peakslocated at. 750 nm and 900nm .